2014
DOI: 10.1088/2041-8205/784/2/l40
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR DISCOVERY OF A CYCLOTRON LINE IN KS 1947+300

Abstract: We present a spectral analysis of three simultaneous Nuclear Spectroscopy Telescope Array and Swift/XRT observations of the transient Be-neutron star binary KS 1947+300 taken during its outburst in 2013/2014. These broadband observations were supported by Swift/XRT monitoring snapshots every three days, which we use to study the evolution of the spectrum over the outburst. We find strong changes of the power-law photon index, which shows a weak trend of softening with increasing X-ray flux. The neutron star sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
63
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 27 publications
(44 reference statements)
15
63
1
Order By: Relevance
“…We caution that this is by no means a detection or a confirmation of a CRSF in the Suzaku data. However, there is a qualitative agreement of the Suzaku data and the results by Fürst et al (2014) regarding the CRSF. Although observed in a number of other sources (e.g., 4U 0115+634 or V 0332+53, Heindl et al 1999;Pottschmidt et al 2005, respectively), we find no indications of a second harmonic, which we would expect around 24 keV, although PIN and NuSTAR are both very sensitive in this energy The best-fit parameters are given in Table 2, and Fig.…”
Section: Phase-averaged Spectroscopysupporting
confidence: 69%
See 3 more Smart Citations
“…We caution that this is by no means a detection or a confirmation of a CRSF in the Suzaku data. However, there is a qualitative agreement of the Suzaku data and the results by Fürst et al (2014) regarding the CRSF. Although observed in a number of other sources (e.g., 4U 0115+634 or V 0332+53, Heindl et al 1999;Pottschmidt et al 2005, respectively), we find no indications of a second harmonic, which we would expect around 24 keV, although PIN and NuSTAR are both very sensitive in this energy The best-fit parameters are given in Table 2, and Fig.…”
Section: Phase-averaged Spectroscopysupporting
confidence: 69%
“…As mentioned above, Fürst et al (2014) discovered a cyclotron line at 12.2 keV in the NuSTAR data. Unfortunately, this is exactly in the gap between the XIS and the HXD spectra.…”
Section: Phase-averaged Spectroscopymentioning
confidence: 60%
See 2 more Smart Citations
“…Spectral parameters are slightly dependent on the source luminosity and in average consistent with a photon index of Γ ∼ 1.1, E cut ∼ 10 keV and E f old ∼ 25 keV (Tsygankov and Lutovinov, 2005b). According to the NuSTAR observations an emission continuum is modified by the pulse phase dependent cyclotron scattering feature at ∼ 12.5 keV Fürst et al (2014a). SWIFT J2000.6+3210 was recently discovered by the Swift/BAT telescope (Tueller et al, 2005) and optically identified with an early BV or mid BIII star (Halpern, 2006;Burenin et al, 2006;Masetti et al, 2008a).…”
Section: Discussionmentioning
confidence: 59%